(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
COVID-19 forced schools to suddenly turn to the new learning system to finish the school year. Unfortunately, this sudden change also changed students’ mental health, specifically those near completion of their college studies. Students have lost social outlets and the learning environment they were accustomed to. In this matter, there is no certainty of when the pandemic will end. In this study, the researchers were able to know the effects of the learning management system on the mental health of the graduating BEED learners at Bestlink College of the Philippines. A descriptive research method was used in conducting this study. Thirty (30) graduating Bachelor of Elementary Education students responded to the survey questionnaires to determine the effects of the Learning Management System on their mental health. The sampling technique used was random sampling, with the data collected through qualitative analysis.